Communication Strategies of FKUB in Managing Conflicts Among Religious Communities in Nganjuk and Kediri - Sutamaji, Sutamaji; Hakim, Lukman (Universitas Islam Tribakti (UIT) Lirboyo Kediri, 2024)
Religious Harmony Forum (FKUB) plays a crucial role in managing diversity to prevent conflicts that could undermine social integrity. Therefore, this study aimed to identify conflict mitigation strategies through communication as well as supporting and hindering factors in the management of interfaith harmony by FKUB Nganjuk Regency and FKUB Kediri City. This qualitative study used various data collection techniques including interviews, observations and documentation. Participants in the study were the leaders of FKUB and representatives of the Nganjuk and Kediri communities. Data analysis used Miles and Huberman's techniques for analysing primary and secondary data, complemented by Stella Ting-Toomey's Face Negotiation Theory to examine face-saving efforts in diversity conflict mitigation. The findings revealed that facework, as a strategy for mitigating diversity conflict through communication, was implemented by considering communication goals and elements. This strategy was manifested in the programmes conducted by the FKUB. The individualistic culture of the community was evident in the conflict management approach of FKUB Nganjuk Regency, while the conflict mitigation approach of FKUB Kediri City was in line with the collectivistic culture of the community. However, both FKUBs also used collectivist approaches to conflict mitigation, particularly through integration. The supporting and hindering factors in managing interfaith harmony stemmed from both internal and external aspects of the FKUB, highlighting the need for synergy between different stakeholders to effectively manage interfaith harmony.